Concurrent durvalumab and radiation therapy (DUART) followed by adjuvant durvalumab in patients with localized urothelial cancer of bladder: results from phase II study, BTCRC-GU15-023. Issue 2 (23rd February 2023) - Joshi, Monika; Tuanquin, Leonard; Zhu, Junjia; Walter, Vonn; Schell, Todd; Kaag, Matthew; Kilari, Deepak; Liao, Jiangang; Holder, Sheldon L; Emamekhoo, Hamid; Sankin, Alexander; Merrill, Suzzane; et al.
Abstract : Background: Patients with bladder cancer (BC) who are cisplatin ineligible or have unresectable disease have limited treatment options. Previously, we showed targeting programmed death-ligand 1 (PD-L1) with durvalumab (durva) and radiation therapy (RT) combination was safe in BC. We now report results from a phase II study evaluating the toxicity and efficacy of durva and RT in localized BC. Methods: This is a single-arm, multi-institutional phase II study; N=26. Enrolled patients had pure or mixed urothelial BC (T2-4 N0-2 M0) with unresectable tumors and were unfit for surgery or cisplatin ineligible. Patients received durva concurrently with RT ×7 weeks, followed by adjuvant durva × 1 year. Primary endpoints: (A) progression-free survival (PFS) at 1 year and (B) disease control rate (DCR) post adjuvant durva. Key secondary endpoints: (A) complete response (CR) post durvaRT (8 weeks), (B) overall survival (OS), (C) PFS and (D) toxicity. Correlative studies included evaluation of baseline tumor and blood (baseline, post durvaRT) for biomarkers. Results: Median follow-up was 27 months. Evaluable patients: 24/26 post durvaRT, 22/26 for DCR post adjuvant durva, all patients for PFS and OS. Post adjuvant durva, DCR was seen in 72.7%, CR of 54.5%. 1-year PFS was 71.5%, median PFS was 21.8 months. 1-year OS was 83.8%, median OS was 30.8 months. CR at 8 weeks post durvaRT was 62.5%. Node positive (N+) patients had similar median PFS and OS. DurvaRT was well tolerated. Grade ≥3 treatment-related adverse events: anemia, high lipase/amylase, immune-nephritis, transaminitis, dyspnea (grade 4-COPD/immune), fatigue, rash, diarrhea and scleritis. No difference in outcome was observed with PD-L1 status of baseline tumor. Patients with CR/PR or SD had an increase in naïve CD4 T cells, a decrease in PD-1+CD4 T cells at baseline and an increase in cytokine-producing CD8 T cells, including interferon gamma (IFNγ) producing cells, in the peripheral blood. Conclusion: Durva with RT followed by adjuvant durva was safe with promising efficacy in localized BC patients with comorbidities, including N+ patients. Larger randomized studies, like S1806 and EA8185, are needed to evaluate the efficacy of combining immunotherapy and RT in BC. Trial registration number: NCT02891161 .